2014
DOI: 10.1097/ncc.0b013e3182a40d8d
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Stage of Adoption for Colorectal Cancer Screening Among African American Primary Care Patients

Abstract: Background Compared with other racial groups, African Americans have the highest colorectal cancer (CRC) incidence and mortality rates coupled with lower screening rates. Objective Our study examined the predictors of stage of adoption for fecal occult blood testing (FOBT) and colonoscopy among African American primary care patients who were non-adherent to published screening guidelines. Methods Baseline data (N = 815) in a randomized clinical trial were analyzed. Participants were categorized into precon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 43 publications
4
35
1
Order By: Relevance
“…Two experimental studies, Christy et al (2013) and Wang and colleagues (2014), obtained the highest MQS of 15 total points. These studies used large (> 300 participants), random (but not nationally representative) samples and multivariate logistic regression modeling for analyses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two experimental studies, Christy et al (2013) and Wang and colleagues (2014), obtained the highest MQS of 15 total points. These studies used large (> 300 participants), random (but not nationally representative) samples and multivariate logistic regression modeling for analyses.…”
Section: Resultsmentioning
confidence: 99%
“…The two-group, clinic-based randomized control trial (RCT) evaluated by Christy and colleagues (2013) did not report any theoretical framework that guided the study, but did report both validity and reliability. Conversely, the RCT consisting of African American primary care patients for the study led by Wang et al (2014) was guided by Stages of Change/Transtheoretical Model and reported the reliability of the data collected, but not the validity. Table 2 presents the theoretical, design, and methodological features of the 19 reviewed studies in detail.…”
Section: Resultsmentioning
confidence: 99%
“…The expanded Health Belief Model has been used extensively to understand cancer prevention and control behaviours, including screening . For many cancers, researchers have documented the influence of perceived risk of the cancer as well as perceived benefits of, perceived barriers to, and self‐efficacy for screening .…”
Section: Health Belief Modelmentioning
confidence: 99%
“…[15][16][17][18][19] For many cancers, researchers have documented the influence of perceived risk of the cancer as well as perceived benefits of, perceived barriers to, and self-efficacy for screening. [16][17][18] As the model predicts, individuals will participate in cancer screening if they believe: (i) they are at risk for a cancer (perceived risk); (ii) screening will reduce the consequences through early detection (perceived benefits); (iii) benefits to participating in screening outweigh the perceived barriers; and (iv) they can accomplish the tasks necessary to complete the screening process (self-efficacy). 20,21 For behaviour change to occur in long-term smokers related to lung cancer screening, individuals must believe they are at risk for lung cancer and that getting screened will benefit them.…”
Section: Health Belief Modelmentioning
confidence: 99%
“…In 2013, 58.2% of adults met the USPSTF CRC guideline, which is well below the Healthy People 2020 target of 70.5% [ 34 ]. Several studies have found the Health Belief and Transtheoretical Models or their constructs applicable and useful to understanding CRC screening behavior [ 35 , 36 , 37 , 38 , 39 , 40 ] and inform the framework for this study. While female breast cancer survivors tend to engage in mammography and colonoscopy screening to a greater extent than non-cancer survivors, opportunities still exist to expand screening and promote other preventive practices [ 41 ].…”
Section: Introductionmentioning
confidence: 99%